Colorimetric Detection of Sulfide Anions via Redox-Modulated Surface Chemistry and Morphology of Au-Hg Nanorods - Xiaotian Zhu; Chang Liu; Jie Liu (International Journal of Analytical Chemistry)
A new colorimetric assay for the detection of sulfide anions with high sensitivity and selectivity is reported, utilizing Au-Hg alloy nanorods (Au-HgNRs) as probe. Au-HgNRs were prepared by modifying gold nanorods (AuNRs) with reducing agent and mercury ions. In an aqueous solution with sulfide anions, the formation of mercuric sulfide due to redox reaction between the amalgams and sulfide anions greatly changed the surface chemistry and morphology of the Au-HgNRs, leading to a red shift of the localized surface plasmon resonance (LSPR) absorption peak, accompanied by a change in colorimetric response. A good linear relationship was obtained between the LSPR peak wavelength shift and concentration of sulfide anion in the range of 1 × 10−5−1 × 10−4 mol/L. The selectivity of this method has been investigated by other anions. The colorimetric sensing system successfully detected sulfide in wastewater from leather industry.